2005
DOI: 10.1029/2004wr003611
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent filtration of bacteria and colloids in porous media

Abstract: [1] Intermittent filtration through porous media used for water and wastewater treatment can achieve high pathogen and colloid removal efficiencies. To predict the removal of bacteria, the effects of cyclic infiltration and draining events (transient unsaturated flow) were investigated. Using physical micromodels, we visualized the intermittent transport of bacteria and other colloids in unsaturated porous media. Column experiments provided quantitative measurements of the phenomena observed at the pore scale.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
67
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(72 citation statements)
references
References 61 publications
4
67
1
Order By: Relevance
“…During wetting, indicators and pathogens were mobilized in the microcosms, perhaps via thin film expansion, air-water interface scouring, and shear mobilization (4,18), suggesting that a fraction of these organisms are capable of being transported to adjacent waters. These mobilized organisms may enter the water column directly (over-beach transport) (74,77) or may be transported through the unsaturated zone of the beach to the water table (through-beach transport) (7).…”
Section: Discussionmentioning
confidence: 99%
“…During wetting, indicators and pathogens were mobilized in the microcosms, perhaps via thin film expansion, air-water interface scouring, and shear mobilization (4,18), suggesting that a fraction of these organisms are capable of being transported to adjacent waters. These mobilized organisms may enter the water column directly (over-beach transport) (74,77) or may be transported through the unsaturated zone of the beach to the water table (through-beach transport) (7).…”
Section: Discussionmentioning
confidence: 99%
“…The adsorption phenomenon is expected to occur at the soil mixture layers in the MSL system. Adsorption is mainly controlled by the surface characteristics of the porous medium, the HLR, the pH, the water content and the surface characteristics of bacterial cells (Auset et al 2005). Filtration and adsorption are the first mechanisms of bacterial removal, followed by other elimination mechanisms such as microbial degradation and the natural death of bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…A comprehensive amount of literature exists on the topic of colloid mobilization and transport in model and natural systems [7,10,14,22,24,27,41,87,88]. Considerable advances have been made on the prediction of colloidal transport using experimental laboratory and field studies as well as numerical models [87,89,90].…”
Section: Stability Of Dispersed Colloidal Particles and Their Transportmentioning
confidence: 99%
“…Considerable advances have been made on the prediction of colloidal transport using experimental laboratory and field studies as well as numerical models [87,89,90]. Laboratory migration experiments [88,90,91] have demonstrated that colloids can migrate with natural flow velocities, although compared to dissolved tracers, their migration is much more sensitive to flow velocity and flow path geometry [92].…”
Section: Stability Of Dispersed Colloidal Particles and Their Transportmentioning
confidence: 99%